TSPO Ligands PK11195 and Midazolam Reduce NLRP3 Inflammasome Activation and Proinflammatory Cytokine Release in BV-2 Cells - Feng, Hao; Liu, Yongxin; Zhang, Rui; Liang, Yingxia; Sun, Lina; Lan, Nannan; Ma, Baoyu (Frontiers in Cellular Neuroscience, 2020)
Neuroinflammation related to microglial activation plays an important role in neurodegenerative diseases. Translocator protein 18 kDa (TSPO), a biomarker of reactive gliosis, its ligands can reduce neuroinflammation and can be used to treat neurodegenerative diseases. Therefore, we explored whether TSPO ligands exert an anti-inflammatory effect by affecting the nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome, thereby inhibiting the release of inflammatory cytokines in microglial cells. In the present study, BV-2 cells were exposed to lipopolysaccharide (LPS) for 6 h to induce an inflammatory response. We found that the levels of reactive oxygen species (ROS), NLRP3 inflammasome, interleukin-1β (IL-1β), and interleukin-18 (IL-18) were significantly increased. However, pretreatment with TSPO ligands inhibited BV-2 microglial and NLRP3 inflammasome activation and significantly reduced the levels of ROS, IL-1β, and IL-18. Furthermore, a combination of LPS and ATP was used to activate the NLRP3 inflammasome. Both pretreatment and post-treatment with TSPO ligand can downregulate the activation of NLRP3 inflammasome and IL-1β expression. Finally, we found that TSPO was involved in the regulation of NLRP3 inflammasome with TSPO ligands treatment in TSPO knockdown BV2 cells. Collectively, these results indicate that TSPO ligands are promising targets to control microglial reactivity and neuroinflammatory diseases.